384-Well Multiplexed Luminex Cytokine Assays for Lead Optimization. (July 2016) - Tang, Huaping; Panemangalore, Reshma; Yarde, Melissa; Zhang, Litao; Cvijic, Mary Ellen
Cytokines serve as a major mechanism of communication between immune cells and are the functional molecules at the end of immune pathways. Abnormalities in cytokines are involved in a wide variety of diseases, including chronic inflammation, autoimmune diseases, and cancer. Cytokines are not only direct targets of therapeutics but also important biomarkers for assessing drug efficacy and safety. Traditionally, enzyme-linked immunosorbent assays (ELISA) were most popular for identifying and quantifying cytokines. However, ELISA is expensive, labor intensive, and low throughput. Here, we report the development of a miniaturized Luminex (Austin, TX) assay platform to establish a panel of high-throughput, multiplexed assays for measuring cytokines in human whole blood. The miniaturized 384-well Luminex assay uses <25% of the assay reagents compared with the 96-well assay. The development and validation of the 384-well Luminex cytokine assays enabled high-throughput screening of compounds in primary cells using cytokines as physiologically relevant readouts. Furthermore, this miniaturized multiplexed technology platform allows for high-throughput biomarker profiling of biofluids from animal studies and patient samples for translational research.